Development of motivational interviewing skills in immunization (MISI): a questionnaire to assess MI learning, knowledge and skills for vaccination promotion - Arnaud Gagneur; Virginie Gosselin; Julie Bergeron; Anne Farrands; Geneviève Baron (Taylor & Francis Group, 2019)
Objective: Vaccine hesitancy is a complex problem. We previously demonstrated that motivational interviewing (MI) could be helpful to enhance parents' motivation to vaccinate their child. The aim of this study is to develop a new, simple and robust evaluation tool that is suitable for evaluating MI learning of vaccination health professionals. Methods: We designed the Motivational Interviewing Skills in Immunization (MISI), a short written questionnaire to evaluate the MI knowledge and skills of participants in an immunization context. It covers three key areas: knowledge of MI, ability to apply MI-related skills, participant self-confidence in using MI. Questionnaire content and face validity were assessed by MI experts and internal consistency, reliability and effect size were analyzed using a multiple pretest-posttest design. Results: Psychometric measures showed good to excellent internal consistency of the questionnaire for all three areas (Cronbach's and KR coefficient: 0.70 to 0.88). Test-retest reliability showed good measurement stability (ICC: 0.53). Good sensitivity to change was also obtained (Cohen's d: 0.80 to 1.66). Conclusion: The MISI questionnaire is the first paper/pencil evaluation method to assess MI training specific to immunization. Psychometric measures showed high reliability. Practice implications: This questionnaire could provide a convenient and inexpensive method to evaluate knowledge and competencies following immunization-specific MI training.